Personality and Cognition in Economic Decision Making - Aurora Garc (Frontiers Research Topics, 2017)
Psychologists studying cognitive processes and personality have increasingly benefited from the wealth of theory, methodology, and decision making paradigms used in economics and game theory. Similarly, for the economists, personality traits and basic cognitive processes offer a set of coherent explanatory constructs in economic behavior. Given the debate on preference invariance and behavioral consistency across contexts and domains, the papers in this topic shed light on the existence and effect of stable sets of idiosyncratic features on economic decision-making. While the effects of personality and cognition on economic decisions remain under-explored, the papers contributed in this topic offer more than a stimulus for further research. The general message could be that personality and cognitive processes offer the stable idiosyncratic ground on which individual decisions are made.